Zooplankton exposure to microplastics at global scale: Influence of vertical distribution and seasonality - Richon, Camille; Gorgues, Thomas; Paul-Pont, Ika; Maes, Christophe (Frontiers in Marine Science, 2022)
Microplastics (MPs) are ubiquitous contaminants in the ocean. Zooplankton is thus widely exposed to MP ingestion. Here, we use a global coupled physical–biogeochemical model enriched with a 3D representation of MPs to assess the global zooplankton exposure to MPs. As expected, our results indicate that water MP concentration is the highest in the surface layers of subtropical gyres and coastal areas close to major MP sources, which is mostly due to floating MPs, while neutral MPs contaminate the mesopelagic zone. Additionally, we showed that floating MPs may be also transported to the mesopelagic waters during the seasonal deepening of the mixed layer depth. We then estimate zooplankton exposure to MPs based on water MP concentrations, plankton biomass, and zooplankton grazing rate. Two main drivers lead to high zooplankton exposure to MPs: 1) high water MP contamination and 2) intense grazing activity. Seasonally, re-stratification of surface waters may lead to MP vertical concentration coinciding with planktonic blooms, thus increasing contamination risk.